2017
DOI: 10.7567/apex.10.103002
|View full text |Cite
|
Sign up to set email alerts
|

Optical control of magnetization dynamics in Gd–Fe–Co films with different compositions

Abstract: Perpendicularly magnetized ferrimagnetic Gd–Fe–Co thin films with different compositions and multilayer arrangements were subjected to femtosecond laser pulses. The pulses triggered different magnetization dynamics in the various thin films. In the Gd26Fe66Co8 film, which has an angular-momentum-compensation temperature (TA) well above ambient temperature (Texp), monotonic magnetization reversal occurred, whereas the Gd22Fe70Co8 film (where TA is well below Texp) exhibited remarkable wavelike spin modulation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Magnetization was calculated using the central differences in (2). The updated equation at time step n is given by:…”
Section: A Multiphysics Simulation For Electromagnetic Fields and Mag...mentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetization was calculated using the central differences in (2). The updated equation at time step n is given by:…”
Section: A Multiphysics Simulation For Electromagnetic Fields and Mag...mentioning
confidence: 99%
“…Recently, the development of devices based on spin dynamics and studies on the magnetic properties of materials have been conducted in the field of magnetic materials [1][2][3][4][5][6][7][8]. In the electromagnetic field analysis of magnetic materials, magnetic permeability is expressed using a constant value, tensor with dispersion, frequency-independent tensor with dispersion, or by solving the Landau-Lifshitz-Gilbert (LLG) equation [2][3][4][5][6]. The permeability tensor is formulated under the assumption that the magnetization in the magnetic material is saturated in a certain direction and constantly moves along a fixed rotation axis [9].…”
mentioning
confidence: 99%
“…2,3) At SPring-8, a variety of materials have been investigated and a large number of outcomes have been produced. [4][5][6][7][8][9][10] A spectroscopic photoemission and low-energy electron microscope [SPELEEM (LEEM III, ELMITEC GmbH)] installed at BL17SU (abranch) is suitable for static image observations with high spatial resolution (∼23 nm under the best conditions). 11) However, since an electron-extraction voltage of −20 kV is applied to a sample, the SPELEEM system is not suitable for creating unusual experimental conditions, e.g.…”
mentioning
confidence: 99%
“…Figures 3(a Even though the space-charging effect is not favorable in the actual analysis, it is confirmed that the resultant images are tolerable for the magnetic domain analysis if the fluence of the applied pulse is at least lower than 20 mJ cm −2 (note that typical fluence required for magnetization control is around 15 mJ cm −2 or lower). 9,19,20) Time-resolved PEEM measurements under other types of stimulation sources such as electric pulses or radiofrequencies are also possible by proper selection of cut-out frequencies of the chopper (1, 3.8, 40 kHz or out of use) and operation modes of the storage The shape of the manipulator tip is compatible with ELMITEC's standard sample cartridges, which are capable of heating samples up to ∼1300 K (∼2000 K for short flashing). A helium/nitrogen-flow cryostat dedicated to lowtemperature experiments is under test experiments.…”
mentioning
confidence: 99%